On Improving the Separation Efficiency of a Wet High Gradient Magnetic Separator for the Removal of Pyrite from Egyptian Coal. Issue 2 (4th March 2017) - Ibrahim, Suzan S.; Selim, Ali Q; Farahat, Mohsen M.; El Menshawey, Ahmed M.; Boulos, Tawfik R.
ABSTRACT: Wet high gradient magnetic separation (WHGMS) of an Egyptian coal sample was carried out to minimize its pyritic-sulfur content reaching 1.60% (2.9% total sulfur). Optimization of the process using the Boxmag Rapid separator included feeding rate, pulp density, applied magnetic field, and the canister loading %. This was conducted through the CCRD and RSM, using Design Expert 6.0 software. Results showed that, at the optimum separation conditions, i.e., 10 l/h feeding rate, 5% pulp density, 2200 Gauss, and 0.6% canister loading, a coal concentrate assaying 0.57% pyritic sulfur was obtained with a recovery 58% and separation efficiency 79.34%.